2016
DOI: 10.1109/tip.2016.2561406
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Impact of Ghosting and Noise on the Perceived Quality of MR Images

Abstract: Magnetic resonance (MR) imaging is vulnerable to a variety of artifacts, which potentially degrade the perceived quality of MR images and, consequently, may cause inefficient and/or inaccurate diagnosis. In general, these artifacts can be classified as structured or unstructured depending on the correlation of the artifact with the original content. In addition, the artifact can be white or colored depending on the flatness of the frequency spectrum of the artifact. In current MR imaging applications, design c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Furthermore, the analysis of variance (ANOVA) can be used to analyse potential differences between participants in terms of scoring. Outtas et al [47], Lévêque et al [3], [55], and Liu et al [34] explicitly conducted such analysis to examine the impact of participants on quality scoring.…”
Section: Data Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the analysis of variance (ANOVA) can be used to analyse potential differences between participants in terms of scoring. Outtas et al [47], Lévêque et al [3], [55], and Liu et al [34] explicitly conducted such analysis to examine the impact of participants on quality scoring.…”
Section: Data Analysis Methodsmentioning
confidence: 99%
“…Low DCT compression rate, low JPEG compression quality, and high JPEG2000 compression rate resulted in high DMOS values, that is to say, poor image quality. Furthermore, a high correlation was found between the DMOS values and thirteen FR-IQA metrics studied, i.e., SNR [22], PSNR [22], SSIM [23], multi-scale SSIM (MS-SSIM) [29], feature similarity index measure (FSIM) [30], information fidelity criterion (IFC) [31], NQM [24], weighted SNR (WSNR) [24], VIF [25], VIF in pixel domain (VIFP) [25], universal image quality index (UQI) [32], information-weighted PSNR (IW-PSNR) [34], and information weighted SSIM (IW-SSIM) [33]. NQM presented the highest correlation (i.e., 0.94), whereas UQI showed a lowest correlation (i.e., 0.81).…”
Section: Magnetic Resonance (Mr) Imagingmentioning
confidence: 99%
“…Some studies on subjective MRI-QA may be found in [3], [4], [6]- [8]. As for objective quality assessment, most efforts apply common reference metrics, such as the Peak Signal-to-Noise Ratio (PSNR) [6], [9]- [12] and the Structural Similarity Index (SSIM) [6], [9], [10].…”
Section: Background and Related Workmentioning
confidence: 99%
“…In the case of MRI, system-related factors include magnetic field (B 0 ) inhomogeneity, electrical system noise or variable coil penetration depths, whilst context factors include resonance frequency shifts between different tissues or inadequate sequence parametrization [2]. Several types of image quality impairments might be induced, including white noise artifacts [3], [4], blurring [2], [3], ghosting [4], inhomogeneities in signal intensities [2] or geometric distortions [2].…”
Section: Introductionmentioning
confidence: 99%
“…Imaging modalities other than x-ray and MRI remain largely ignorant of the task-specific approach and instead rely on the pIQ, 10 while making the assumption that perceived quality is correlated with clinical performance. In fact, a number of studies continue to this day using pIQ, even in x-ray 11 and MR imaging 12 …”
Section: Introductionmentioning
confidence: 99%